Developing young children's computational thinking with educational robotics: An interaction effect between gender and scaffolding strategy - Angeli, Charoula; Valanides, Nicos (Computers in human behavior, 2020)
The study examined the effects of learning with the Bee-Bot on young boys' and girls' computational thinking within the context of two scaffolding techniques. The study reports statistically significant learning gains between the initial and final assessment of children's computational thinking skills. Also, according to the findings, while both boys and girls benefited from the scaffolding techniques, a statistically significant interaction effect was detected between gender and scaffolding strategy showing that boys benefited more from the individualistic, kinesthetic, spatially-oriented, and manipulative-based activity with the cards, while girls benefited more from the collaborative writing activity. In regards to the children's problem-solving strategies during debugging, the results showed that the majority of them used decomposition as a strategy to deal with the complexity of the task. These results are important, because they show that children at this very young age are able to cope with the complexity of a learning task by decomposing it into a number of subtasks that are easier for them to tackle. The research contributes to the body of knowledge about the teaching of computational thinking. In addition, the study has practical significance for curriculum developers, instructional leaders, and classroom teachers, as they can use the results of this study to design curricula and classroom activities with a focus on the broader set of computational thinking skills, and not only coding. •The study examined the effects of learning with the Bee-Bot on computational thinking.•A gender-friendly learning environment was designed.•An interaction effect was found between gender and scaffolding strategy.•Young children used decomposition as a problem-solving strategy during debugging.